The role of pharmacotherapy, rehabilitation and nutrition in the treatment of children with West syndrome - Smyk, Paulina; Barczykowska, Ewa; Zreda-Pikies, Aneta; Ulenberg, Agata; Kurylak, Andrzej (Journal of Education, Health and Sport, 2018)
West syndrome is classified as an epileptic encephalopathy. This syndrome is diagnosed in children aged 4-6 months. Its unsuccessful prognosis and complicated aetiology affects the delay of psychomotor development and cognitive functions of children. Repeated attacks inhibit the realization of next tasks assigned to the children’s age. Properly conducted treatment of West syndrome should be interdisciplinary and include pharmacological treatment, diet and rehabilitation. Pharmacological treatment of West syndrome includes: the ACTH hormone, corticosteroids (prednisolone), vigabatrin, valproic acid, nitrazepam, pyridoxine, zonisamide, topiramide. The therapy includes also a ketogenic diet which assumes changes in the proportion of nutrients. Predominant ingredient in the diet are fats (80-90% of daily intake of nutrients). Further, children with West syndrome require neuropsychological and motor rehabilitation (Vojta therapy, NDT- Bobath therapy). Cooperation of therapeutic experts with parents of the children makes it possible to achieve therapeutic benefits through improvement of the children's quality of life. Mental disability and cognitive impairment associated with the syndrome result in the loss of skills already acquired by children, therefore motivation and support of the children's parents is a significant task assigned to therapeutic team members.